Common Structural Elements in the Chromophore Binding Pocket of the Pfr State of Bathy Phytochromes1. (13th May 2017) - Velázquez Escobar, Francisco; Buhrke, David; Michael, Norbert; Sauthof, Luisa; Wilkening, Svea; Tavraz, Neslihan N.; Salewski, Johannes; Frankenberg‐Dinkel, Nicole; Mroginski, Maria Andrea; Scheerer, Patrick; Friedrich, Thomas; Siebert, Friedrich; et al.
Abstract: Phytochromes are bimodal photoreceptors which, upon light absorption by the tetrapyrrole chromophore, can be converted between a red‐absorbing state (Pr) and far‐red‐absorbing state (Pfr). In bacterial phytochromes, either Pr or Pfr are the thermally stable states, thereby constituting the classes of prototypical and bathy phytochromes, respectively. In this work, we have employed vibrational spectroscopies to elucidate the origin of the thermal stability of the Pfr states in bathy phytochromes. Here, we present the first detailed spectroscopic analysis of Rp BphP6 ( Rhodopseudomas palustris ), which together with results obtained for Agp2 ( Agrobacterium tumefaciens ) and Pa BphP ( Pseudomonas aeruginosa ) allows identifying common structural properties of the Pfr state of bathy phytochromes, which are (1) a homogenous chromophore structure, (2) the protonated ring C propionic side chain of the chromophore and (3) a retarded H/D exchange at the ring D nitrogen. These properties are related to the unique strength of the hydrogen bonding interactions between the ring D N‐H group with the side chain of the conserved Asp194 ( Pa BphP numbering). As revealed by a comparative analysis of homology models and available crystal structures of Pfr states, these interactions are strengthened by an Arg residue (Arg453) only in bathy but not in prototypical phytochromes. Abstract : A vibrational spectroscopic and structural analysis of bathy phytochromes reveals that the unique thermal stability of the Pfr state roots in the particular hydrogen bonding interactions of the ring D N‐H group of the biliverdin cofactor with the side chain of conserved Asp. In contrast to prototypical phytochromes, these interactions are further strengthened by an Arg residue that is conserved in bathy phytochromes. This specific hydrogen bond complex accounts for the rigid fixation of the biliverdin in the chromophore binding pocket and impairs thermal isomerization to the Pr state.